Evaluating the Success of Bank Jago Digital Banking Application using an Integrated DeLone and McLean and TAM Model - Dessy Elvyana; Zarnelly Zarnelly; Tengku Khairil Ahsyar; Nesdi Evrilyan Rozanda; Angraini Angraini (UIN Sumatera Utara, 2026)
The rapid growth of digital banking in Indonesia has increased the need to evaluate the success of digital banking applications from both information system and user acceptance perspectives. Despite its widespread adoption, Bank Jago users continue to report issues related to system performance and service quality. This study evaluates the success of the Bank Jago application by integrating the DeLone and McLean Information Systems Success Model with the Technology Acceptance Model (TAM). A quantitative survey of 100 Bank Jago users in Pekanbaru, recruited through non-probability accidental sampling, was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4; this geographic and sampling scope bounds the generalizability of the findings. Seven of the nine hypotheses were supported; Information Quality did not significantly affect User Satisfaction, and Perceived Usefulness did not significantly affect Behavioral Intention to Use. The model explained a substantial proportion of variance in User Satisfaction (R2 = 0.752), and the strongest reported standardized relationship was User Satisfaction on Net Benefit (Beta = 0.747), which is a single-predictor path and should be interpreted with that structural prominence in mind. These findings support the integrated DeLone and McLean and TAM framework in the digital banking context and indicate that Bank Jago should prioritize system quality, service quality, and application usability to enhance user satisfaction and the benefits perceived by users.